Potensi Pengembangan Usaha Peternakan Sapi Babussalam Al Barokah Pada Kawasan Sapi Ternak Di Kabupaten Bogor - Puti Lenggo Ginny; Canggih Gumanky Farunik; Tjong Se Fung (Komunitas Dosen Indonesia, 2021)
Dairy Farming Business experienced an increase in production as of 2017, but was only able to meet 22% of the national milk consumption needs in the same year. This is in the perspective of a business feasibility study, it is considered that it has not maximized its potential. The main reason why the national milk demand is high is the high dependence of dairy farmers on the milk processing industry. On the other hand, the milk processing industry itself prioritizes imported raw materials. This situation will not be profitable for cattle farmers, where they are like